TRADISI REWANG DALAM ADAT PERKAWINAN KOMUNITAS JAWA DI DESAPETAPAHAN JAYA SP-1 KECAMATAN TAPUNG KABUPATEN KAMPAR - Sri Puspa Dewi; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study is about "Rewang tradition as in the implementation of javanese wedding party". This study intends to explain about rewang tradition as the social exchange in society in the implementation of wedding party, and the exchange tradition between one people comunity with others in the implementation of javanese wedding party. This study is located in village of Petapahan Jaya Sp-1 Tapung Kampar.In this study, the author used qualitative descriptive type of research that describes and explains the data through reasoning based logic to logical conclusions about the data being analyzed, so can to show a systematic picture of the situation about factors assosiated with the phenomenon being examined without use count statisticts. Data collection techniques is using snowball, observation interviews and documentation. Based on the data analysis, the conclusion of the rewang tradition about the exchange sistem is there are reciprocal exchange and happened so long. Then the people often refer to it as savings in the future when someday people will hold the wedding party. In the rewang tradition the things whose exchanged is not money but the things whose contents raw materials for fulfillment of the presentment in the implementation of wedding party.Keywords: Rewang, Marriage Custom, Traditional Javanese